Traumatic Dissociation as a Predictor of Posttraumatic Stress Disorder in South African Female Rape Survivors. Issue 16 (April 2015) - Nöthling, Jani; Lammers, Kees; Martin, Lindi; Seedat, Soraya; Jain., Gaurav
<x xml:space="preserve">Abstract</x> Abstract Women survivors of rape are at an increased risk for posttraumatic stress disorder (PTSD). Traumatic dissociation has been identified as a precursor of PTSD. This study assessed the predictive potential of traumatic dissociation in PTSD and depression development. The study followed a longitudinal, prospective design. Ninety-seven female rape survivors were recruited from 2 clinics in Cape Town, South Africa. Clinical interviews and symptom status assessments of the participants were completed to measure dissociation, childhood traumas, resilience, depression, and PTSD. Traumatic dissociation was a significant predictor of PTSD and depression. The linear combination of prior dissociation, current dissociation, and resilience significantly explained 20.7% of the variance in PTSD. Dissociation mediated the relationship between resilience and PTSD. As traumatic dissociation significantly predicts PTSD, its early identification and management may reduce the risk of developing PTSD. Interventions focused on promoting resilience may also be successful in reducing the risk of dissociation following rape.